216k views
0 votes
In the equation 6x − 2 = −4x + 2, Spencer claims that the first step is to add 4x to both sides. Jeremiah claims that the first step is to subtract 6x from both sides. Who is correct? Explain.

2 Answers

2 votes

Answer:

Both are true. Both methods will produce the same solution as long as inverse operations and equality properties are used correctly. They are both able to isolate the variable on one side of the equation.

Explanation:

User Patrick Read
by
5.8k points
2 votes

Answer:

Both Of Them

Explanation:

You can start on either side to solve for x. It will get you the same answer.

Spencer

6x - 2 = -4x + 2

+4x +4x

10x - 2 = 2

+2 +2

10x = 4

x = .4 or
(2)/(5)

Jeremiah

6x - 2 = -4x + 2

-6x -6x

-2 = -10x + 2

-2 -2

-4 = -10x

x = .4 or
(2)/(5)

User Yanchenko
by
5.8k points